The cognitive load of listening activities of a cognitive-based listening instruction - Rahimi, Mehrak; Sayyadi, Mehran (Universitas Pendidikan Indonesia, 2019)
The aim of this study was to investigate the cognitive load (henceforth, CL) of listening activities of a cognitive-based listening instruction of a recently changed EFL curriculum. 126 K-11 students (male=62, female=64) participated in the study. The quantitative and qualtivative data were collected and analyzed in two phases. In phase 1, the participants were asked to judge the CL of listening activities of their textbook based on the CL measure immediately after completeling the tasks. The scale has 10 items that measure three components of CL including Intrinsic Load (IL), Extraneous Load (EL), and Germane Load (GL). The data were analyzed by Multivariate Analysis of Variance (MANOVA). The result primarily revealed that the general cognitive load of listening activities was rather high and when three kinds of CLs were compared, the GL was found to be higher than IL and EL. Comparing the CL of male and female students revealed that there is a signficant difference between the two groups regarding general CL and both IL and EL; and as the GL of both groups was high, no signficant difference was observed between their GL. In pahse 2 of the study, 14 students participated in a structured interview to express their opinions about the difficulty of listening comprehension. The rate of speech and unintelligibility of the speakers’ pronunciation, insufficient technological infrastructures, lack of interest in and negative attitudes towards listening, and limited multidmodal input were among the factors that students felt to contribute to the difficulty of listening comprehension.